KANK1 shapes focal adhesions by orchestrating protein binding, mechanical force sensing, and phase separation - Kaitong Guo; Jing Zhang; Pei Huang; Yuqun Xu; Wenfei Pan; Kaiyue Li; Lu Chen; Li Luo; Weichun Yu; Shuai Chen; Sicong He; Zhiyi Wei; et al. (Cell Reports, 2023)
Summary: Focal adhesions (FAs) are dynamic protein assemblies that connect cytoskeletons to the extracellular matrix and are crucial for cell adhesion and migration. KANKs are scaffold proteins that encircle FAs and act as key regulators of FA dynamics, but the molecular mechanism underlying their specified localization and functions remains poorly understood. Here, we determine the KANK1 structures in complex with talin and liprin-β, respectively. These structures, combined with our biochemical and cellular analyses, demonstrate how KANK1 scaffolds the FA core and associated proteins to modulate the FA shape in response to mechanical force. Additionally, we find that KANK1 undergoes liquid-liquid phase separation (LLPS), which is important for its localization at the FA edge and cytoskeleton connections to FAs. Our findings not only indicate the molecular basis of KANKs in bridging the core and periphery of FAs but also provide insights into the LLPS-mediated dynamic regulation of FA morphology.